FROM EXPOSURE TO ONCOGENESIS: THE ROLE OF MICROPLASTICS AND ASSOCIATED POLLUTANTS IN CANCER - A LITERATURE REVIEW - Grzegorz Przywara,; Oliwia Biegańska,; Emilia Biczak,; Hanna Barska-Kobylińska,; Martyna Byrska,; Marta Janura,; Maja Weimann,; Maciej Ziomek, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Microplastics (MPs) are defined as particles smaller than 5 mm. They are ubiquitous environmental pollutants. They enter the human body primarily through food, water and inhaled air. This paper focuses on a collection of scientific studies concerning the accumulation of MPs in human tissues and their impact on cancer development, also considering the role of MPs as carriers of known carcinogens.Brief description of the state of knowledge: In recent years, MPs have attracted considerable scientific attention. Their effects on human health, including oncology, have begun to be investigated. This area remains poorly studied, although new publications are emerging rapidly. Systematic reviews specifically addressing the oncological consequences of MPs are also lacking. Therefore, we see the need to summarize the current state of knowledge in this aspect.Summary (conclusions): Increased levels of polyethylene (PE), polypropylene (PP), polystyrene (PS) and polyvinyl chloride (PVC) have been detected in tumor tissues such as breast, colorectal, pancreatic, prostate, lung and cervical cancers. In vitro and in vivo studies show that MPs stimulate tumorigenesis by enhancing cell proliferation, epithelial-mesenchymal transition, migration and activation on oncogenic PI3K/AKT and MAPK/ERK pathways. Moreover, MPs can serve as vectors for carcinogens (for example, polycyclic aromatic hydrocarbons and bisphenols). We hope this review will help guide future research directions.